Analisis Manajemen Portofolio Obligasi sebagai Portofoilo Aset pada PT Bank Negara Indonesia, Tbk - , Ikhwani Fauzana ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bonds is one of the most important assets for banks because a significant portion and can provide interest income that was quite interesting. Capital market development is quite rapid at this time greatly affects the volume of bond transactions in both the primary and secondary markets in which one is the banking capital market. Currently PT. Bank Negara Indonesia, Tbk has bonds with varying types of both government bonds and corporate bonds. This thesis discusses the existing bond portfolio management at PT. Bank Negara Indonesia, Tbk through analysis of portfolio risk and performance analysis of bond portfolios. The result of the analysis is the performance bond portfolio owned by PT. Bank Negara Indonesia, Tbk is increasing from year 2009 - 2011, although still quite low when compared with the index yield bond market. Bond portfolio's risk profile varies from low to high risk, but there is still some kind of risk has not been mitigated. This is one of the factors causing the performance bond portfolio pt. Bank Negara Indonesia, Tbk has not been able to exceed the performance of the bond market index.